The Daniel Wilsons in France, 1819-1919 - Palmer, Michael, 1946- author.
1 online resource (x, 244 pages)
Keywords: "Scottish engineer Daniel Wilson (1790-1849) helped launch the industrial revolution in France and acquired a major art collection. His daughter, Marguerite (1836-1902), restored the château de Chenonceau, near the Loire Valley. His son, Daniel (1840-1919), close to Marguerite, became an MP, founded a newspaper chain, rose to become a leading republican politician, and married the daughter of President of the Republic Jules Grévy. The younger Daniel Wilson's business activities and news strategies offended many and prompted his involvement in a scandal (the sale of the Legion of Honour decoration) that led to his downfall and that of President Grévy. Wilson's name became and remains synonymous with political corruption. This book is the first to examine the nexus of political and press connections in early republican France from his viewpoint. The struggle for press freedom since the 1789 Revolution culminating in the 1881 Press Law is assessed by considering the stance of Wilson, Grévy, the leading press magnate Emile de Girardin and other press tycoons. The flamboyant Marguerite, who hosted Gustave Flaubert in Chenonceau and journeyed to India, colors the saga"--